ANALISIS ISOENZIM UNTUK MEMPELAJARI VARIASI GENETIK SAPI BALI DI PROVINSI BALI - Sri Rahayu; SB Sumitro; T. Susilawati; Soemarno Soemarno (The East Java Biological Society, 2006)
The aim of this research was to know Bali cattle genetic variation according to the band pattern of isoenzyme. Esteraseand Malate dehydrogenase Isoenzymes of Bali cattle were studied. Using the native-PAGE method, the analysis has been made of the genetic structure and variation of the bali cattle population. Isoenzyme isolated from leucocytes cell using homogenation method by adding Phosphat Buffer Saline (PBS). A hundred sample of Bali cattles were taken in Mambang, Slemadeg and Kuwumkeladi. The result of this research indicate that from the 2 different enzyme, 3 loci were detected, and 1 of them was polymorphic (MDH-2). There was null allele phenomenom in MDH-2 locus. The loci polymorphic proportion of three population were 0,333. Chi-Square analysis of three population were 1.251–1.560. The heterozygosity value of three population (Mambang, Slemadeg and Kuwumkeladi) were 0.098, 0.111 and 0.118, respectively.